Diet and Endometriosis: A Comprehensive Review of Current Evidence - Kuczma, Matylda; Kamińska, Marta; Klimczak, Adrianna; Pietrzak, Barbara; Patelski, Mikołaj; Czapla, Maciej; Surma, Mateusz; Molenda, Jakub; Mikusek, Wiktoria; Kotlarz, Wiktoria (Quality in Sport, 2026)
Endometriosis is a chronic, estrogen-dependent inflammatory disease affecting 10% of women of reproductive age. Patients often experience symptoms such as pelvic pain, dysmenorrhea, gastrointestinal disturbances, and infertility. Conventional treatment methods, including hormonal therapy and surgery, offer limited relief and high recurrence rates. Dietary interventions have gained interest as potential adjuncts to symptom management. This study reviews current evidence on the impact of diet on the development, symptom severity, and progression of endometriosis, focusing on specific nutrients, dietary patterns, and elimination diets. A literature search was conducted using PubMed and Google Scholar for English-language, peer-reviewed studies published up to 2025. Keywords were “Endometriosis”, “Diet”, “Gluten-free”, “Vitamin D”, “Omega-3”, “FODMAP Diet”. Original research articles, randomized controlled trials, and systematic reviews (only if original data were also reported) were analysed. Anti-inflammatory, antioxidant-rich diets are associated with symptom reduction. Omega-3 fatty acids show protective effects, while high consumption of red meat and trans fat may increase the risk of endometriosis. Vitamin D shows potential benefits in experimental models, but clinical evidence remains inconclusive. Gluten-free and low-fermentable oligo-, di-, monosaccharide and polyol (FODMAP) diets may relieve gastrointestinal symptoms in selected patients, but should be implemented with caution. Dairy products and dietary fiber may offer protective effects, though data remain inconsistent. While current evidence suggests that diet may influence endometriosis, most data remain observational. Further randomized controlled trials are needed to confirm causality and develop evidence-based dietary guidelines for endometriosis management.